The use of smart board media and number windmill to improve students’ understanding of addition concepts in madrasah ibtidaiyah - Farida, Siti Nur; Nahrowi, Moh. (Mitra PGMI: Jurnal Kependidikan MI, 2025)
students through the use of innovative learning media in the form of a smart board and number windmill. The main issue identified at MI Bustanul Ulum 06 Gumukmas is the low arithmetic ability of students, particularly in grasping basic addition concepts. This research employs a qualitative approach using the Research and Development (R&D) method, referring to the ADDIE development model, which includes five stages: analysis, design, development, implementation, and evaluation. The media is designed to incorporate visual, auditory, and kinesthetic elements to stimulate the learning interest of students aged 7–10 years. Based on trial results, the media was found to be highly feasible, with an eligibility score of 94%. The use of this media effectively increased students' enthusiasm and active participation in learning and facilitated a better understanding of addition through a fun and concrete approach. Therefore, the use of the smart board and number windmill is effective in supporting the learning process of mathematics at the Madrasah Ibtidaiyah level.